Optical detection of an ensemble of C centres in diamond and their coherent control by an ensemble of NV centres. (October 2021) - Rubinas, O.R.; Soshenko, V.V.; Bolshedvorskii, S.V.; Cojocaru, I.S.; Zeleneev, A.I.; Vorobyov, V.V.; Sorokin, V.N.; Vins, V.G.; Smolyaninov, A.N.; Akimov, A.V.
Abstract: The nature of decoherence in a diamond plate that is most optimal for magnetometry (i.e., a plate with compromise values of concentration and coherence time of NV centres) is investigated in detail. The concentration of C centres, which serve as donors for the formation of NV centres and at the same time limit their coherence time, is measured in this plate. The ensemble of NV centres in diamond is used as a sensing element, which makes it possible to record the coherence dynamics and concentration of C centres. The recording is performed using the double electron – electron resonance technique. Its significant advantage over IR spectroscopy, which yields some averaged concentration of defects in diamond, is the possibility of measuring locally the concentration of C centres. The method proposed by us yields a value of 50.1 ± 1.4 ppm for the C-centre concentration, which refines the IR spectroscopy data (57.5 ± 4.8 ppm).